Patient Safety Culture in The Inpatient Installation of Dr. R. Hardjanto Hospital Balikpapan - Herlina, Melania; Musdalifah, Musdalifah; Apriyatmoko, Raharjo (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
Patient safety has become a global concern in healthcare systems, particularly in hospital settings where the risk of adverse events remains significant. This study aims to analyze the patient safety culture among nurses in the inpatient installation of Dr. R. Hardjanto Hospital Balikpapan and its relationship with the implementation of healthcare services. A descriptive quantitative design was applied in this study. The population consisted of all nurses working in the inpatient installation, with a total sample of 75 respondents selected using proportionate stratified random sampling. Data were collected through structured questionnaires measuring various dimensions of patient safety culture, including teamwork, communication, leadership support, non-punitive response to errors, and incident reporting. The results showed that 50.7% of respondents had a high level of patient safety culture, while 49.3% were categorized as low. Several dimensions such as organizational learning (85.3%), feedback on errors (84%), and teamwork across units (92%) were categorized as high. However, some aspects including non-punitive response to errors (42%), staffing adequacy (44%), and patient handover (49.3%) were still considered low. In terms of service implementation, 69.3% of respondents demonstrated good performance, while 30.7% showed poor performance. The findings also revealed that nurses with a high level of patient safety culture consistently performed better in delivering healthcare services. This study concludes that patient safety culture significantly influences the quality of healthcare service delivery. Strengthening weak dimensions of patient safety culture, improving leadership roles, ensuring adequate staffing, and promoting a non-punitive reporting environment are essential to enhance patient safety outcomes. These findings provide valuable insights for hospital management to develop strategies aimed at improving patient safety culture and service quality.